Program KKN Tematik: Sosialisasi Pemuda Berkarakter, Agen Perubahan, Dan Anti-Korupsi Bersama Civitas AMGPM - Sherynzwing Margareth Tuahatu; Frisca Claudia Tumury; Stivano Joris (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Real Work Lectures (KKN) are a form of community service carried out by students as part of academic activities at Indonesian universities, especially in the aspect of human resource development. This aims to form a young generation with integrity, responsibility and a high awareness of the values ​​of honesty and transparency. One of the programs implemented is "Socialization to Build the Young Generation as Youth with Character, Agents of Change & Anti-Corruption from an Early Age" which includes anti-corruption counselors. This socialization applies formal educaation methods, case studies and joint discussions designed to instill anti-corruption values ​​and encourage the proactive role of youth as agents of change. The implementation of this program shows an increase in the younger generation's understanding and concern for social issues, as well as strengthening their character as future leaders who are ready to maintain their integrity and contribute positively to society. It is hoped that this program can be a strategic step in developing a young generation who is ready to play an active role in advancing the nation in a sustainable and corruption-free manner.